2010
DOI: 10.4103/0019-557x.77266
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of stress among resident doctors working in Medical Colleges of Delhi

Abstract: The present cross-sectional study was conducted from November 2007 to December 2008 in four medical colleges and associated hospitals of Delhi. Study subjects comprised 930 resident doctors. The overall prevalence of stress was found to be 32.8% in resident doctors from all colleges. Out of 930 resident doctors, 165 (17.7%) had mild stress, 113 (12.2%) had moderate stress, and 27 (2.9%) were severely stressed. Important reasons of stress as perceived by the study subjects included long duty hours, departmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 0 publications
8
56
4
Order By: Relevance
“…14 Similar finding were also found in other study 10 .A study done by Bansal RK et al showed that maximum stress feeling was reported by the 1 st year residents (77.3%) followed by 52.1% among the 2 nd year and 58.31% among the 3 rd year students respectively. 9 Our study showed that stress level found 33.33% (55) in clinical post graduates as compared pre and para clinical post graduates.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…14 Similar finding were also found in other study 10 .A study done by Bansal RK et al showed that maximum stress feeling was reported by the 1 st year residents (77.3%) followed by 52.1% among the 2 nd year and 58.31% among the 3 rd year students respectively. 9 Our study showed that stress level found 33.33% (55) in clinical post graduates as compared pre and para clinical post graduates.…”
Section: Discussionsupporting
confidence: 79%
“…Similar results were found in a study done by Saini NK et al 10 showed that out of 930 doctors majority were in 26-30 years of age constituting about 69% (642).While in an another study 74 (58.7%) were in 30-39 years of age. 11 Our Study showed that females are more stressed as compared to males .It is found statistically significant.…”
Section: Discussionsupporting
confidence: 78%
“…We think this pattern may rather be a consequence of work strain and depression leading to workers absenteeism. A study conducted by Saini et al [4] also proved that work-related depression was a product of stress and job dissatisfaction. Lack of social support and resources, little control and autonomy on the job, and unfair and overly demanding workloads and expectations could breed depression.…”
Section: Ijomeh 2014;27(6)mentioning
confidence: 99%
“…JCQ-K is a questionnaire-based instrument designed to measure the content of a work task. It contains 5 scales: psychological demand (job demand), decision latitude health sector employees [3,4]. Low labor costs, easy supply of leather and a tradition of shoe making allowed shoe manufacturing industries to move to developing countries.…”
Section: Research Instruments and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation